Bill Content, Legislative Outcomes, and State-Level Resistance to National Policies. Issue 4 (30th December 2021) - Callaghan, Timothy; Karch, Andrew
Abstract: Recently, scholars of the lawmaking process have urged their colleagues to devote more attention to the potential impact of bill content on legislative outcomes. Heeding their call, this paper builds an original dataset of over 5, 000 pieces of state-level legislation addressing issues that span the ideological spectrum. It compares proposals that challenge the authority of the national government in a specific domain to proposals that lack federalism-related implications and finds that the former, all else being equal, make less legislative progress toward enactment. In addition, it categorizes the measures that resist national laws based on the specific nature of the challenge they pose. Its analysis finds that measures that are inconsistent with existing national law but work within the law's legal framework make more legislative progress than measures that seek to nullify the national law or that vow not to cooperate with it. It also confirms that sponsor characteristics such as majority status, the number of cosponsors, institutional rules such as hearing requirements, and state-level factors like party control of the state legislature affect how much progress proposals make toward enactment. Thus, the paper demonstrates the importance of legislative content as an explanatory factor and sheds light on the nature of intergovernmental relations in the contemporary United States.